İstanbul’daki Acem Matbaalarının Bir Örneği Olarak Hurşid Matbaası ve Faaliyetleri - YILDIZ, GÜLLÜ (My University, 2024)
Bu makale Osmanlı matbuat tarihinin bilinmeyen aktörlerinden biri olarak Muhammed Mehdi Tebrizî’yi hayatı ve Hurşid matbaası merkezli yayıncılık faaliyetleriyle tanıtmayı amaçlamaktadır. Bunun için öncelikle Muhammed Mehdi’nin biyografisine yer verilerek kimliği hakkındaki belirsizlikler tartışılmış ve ardından yayıncılık faaliyetleri bütün yönleriyle tespit edilmeye çalışılmıştır. Sahibi olduğu Hurşid matbaasının tarihini ve bu matbaada bastığı kitapların tam bir listesini oluşturabilmek için arşiv belgelerinin yanı sıra basılan kitapların künye bilgilerine başvurulmuştur. Son olarak Muhammed Mehdi’nin yayıncılık faaliyetlerinin boyutunu değerlendirebilmek amacıyla Ahter matbaasıyla irtibatı ele alınmıştır. Anahtar Kelimler: İstanbul, Acemler, Yayıncılık, Muhammed Mehdi Tebrizî, Hurşid Matbaası

This article aims to introduce Muhammad Mahdi Tabrizi as a previously unknown actor in the history of the Ottoman printing press through his life and the publishing activities centered around the Khurshid printing house. To achieve this, the article first presents a biography of Muhammad Mahdi, discussing issues related to his identity. It then seeks to detail every aspect of his publishing activities. Utilizing archival materials and the imprints of the printed books, the article compiles a history of the Khurshid printing house and provides a comprehensive inventory of the books he printed. Finally, the article analyzes Mahdi’s association with the Akhtar printing house to evaluate the scope of his publishing endeavors. Keywords: Istanbul, Persians, Ajams, Publication, Muḥammad Mahdī Tabrīzī, Khurshid Printing House
Khurshid Press in the Context of Persian Printing Houses in Istanbul
Keywords: Istanbul; Persians; Ajams; Publication; Muḥammad Mahdī Tabrīzī; Khurshid Printing House; İstanbul; Acemler; Yayıncılık; Muhammed Mehdi Tebrizî; Hurşid Matbaası